2008
DOI: 10.1097/yct.0b013e318158792f
|View full text |Cite
|
Sign up to set email alerts
|

A Dissociation Between Anterograde and Retrograde Amnesia After Treatment With Electroconvulsive Therapy

Abstract: Results of the study suggest that a clinical course of ECT is associated with isolated impairment for information learned before treatment (ie, retrograde memory), whereas there was no effect of ECT on posttreatment learning abilities (ie, anterograde memory).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…In addition, we observed no retrograde amnesia. While the prevalence, severity, and duration of retrograde amnesia remains unknown, recent investigations have consistently reported the presence of this memory impairment post‐ECT . In regards to immediate post‐MST effects, the initial four patients awoke from the anesthetic fully oriented in a manner notably different from what is typically seen post‐ECT.…”
Section: Discussionmentioning
confidence: 96%
“…In addition, we observed no retrograde amnesia. While the prevalence, severity, and duration of retrograde amnesia remains unknown, recent investigations have consistently reported the presence of this memory impairment post‐ECT . In regards to immediate post‐MST effects, the initial four patients awoke from the anesthetic fully oriented in a manner notably different from what is typically seen post‐ECT.…”
Section: Discussionmentioning
confidence: 96%
“…Research has suggested that the confusion after each ECT treatment and the anterograde amnesia are time-limited (11-15), but retrograde amnesia has been found to persist up to and past 6-months in some cases (11-15). Patient-specific factors including greater age (16), lower education level, and lower premorbid intelligence (17) may increase the level of cognitive impairment associated with ECT.…”
Section: Electroconvulsive Therapymentioning
confidence: 99%
“…Using this technique, O’Connor et al were able to show that retrograde memory, but not anterograde memory, was somewhat impaired. 33 The study was not designed to evaluate long-term personal memory or unilateral/bilateral differences. It would have been interesting if the researchers had included a second control sample of depressed patients who were receiving medication instead of ECT.…”
Section: Commentarymentioning
confidence: 99%